Մեծարենցեան երազի եւ տեսիլի լեզուաոճական առանձնայատկութիւնները - Առաքելեան, Կարինէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Мечта и видение сопровождают человечество с момента его сотворения и играли особую роль на протяжении всей истории, особенно в тяжелые и нестабильные времена. Для армянского народа одним из таких периодов стал рубеж XIX—XX веков. Не случайно именно тогда в восточной и западной ветвях армянской литературы наблюдался расцвет поэзии, связанной с образами снов и видений, а также появление талантливых поэтов. Dreams and visions have been known to humanity since the dawn of creation and have accompanied it throughout history. These phenomena were especially prominent during difficult and turbulent times, such as the early 20th century for the Armenian people. It is no coincidence that during this period, poetry, as well as literature centered on dreams and visions, experienced an unprecedented rise in both Eastern and Western Armenian literary traditions, giving rise to many talented poets.
Keywords: Հաղորդումներ; Բանասիրութիւն